MANAJEMEN PRIVASI KOMUNIKASI MAJLIS SEMA’AN AL-QUR’ĀN JANTIKO MANTAB DAN DZIKRUL GHŌFĪLĪN - Santoso, Bobby Rachman (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2019)
This research purpose to describe the communication of the Majlis Sema'an Al-Qur'ān Jantiko Mantab and Dzikrul Ghōfīlīn in their position as a group that has influential religious activities and is in the public interest.By using communication privacy management theory, the author tries to explain the dialectical process carried out by MSQ Jantiko Mantab and Dzikrul Ghōfīlīn in developing their activities.The result, that MSQ Jantiko Mantab and Dzikrul Ghōfīlīn conducted the opening of private information with direct and indirect communication.They congregation conducted the opening of private information aimed at clarifying misunderstandings regarding the activities of the MSQ of Jantiko Mantab and Dzikrul Ghōfīlīn. Information disclosure also purpose to develop the MSQ Jantiko Mantab and Dzikrul Ghōfīlīn in various regions. It was proven that initially only a few people attended, now thousands of people followed, and their activities were carried out in various regions, especially East Java.